Can Rights be Enough? - Rebecca Ploof (Global justice: Theory, Practice, Rhetoric)
The climate crisis is beset by depoliticization. Couched as an issue that experts must solve through technological or technocratic knowledge, discussion about how to address environmental degradation is not amenable to democratic action or dissensus. This paper argues that approaching climate change through a human rights framework risks reinscribing such depoliticization and that this is politically hazardous. Human rights discourse can impede the demos’ exercise of power, obscure exercises of hegemony, and, via a fixed notion of progress, discourage normative contestation. This discourse’s depoliticizing potential is further attested to by the debate over human rights’ relationship to the depoliticizing ideology of neoliberalism. Moreover, beyond the language of human rights, the larger legal phenomena of judicialization and juridification may further contribute to depoliticization.  Depoliticization is risky because it can provoke politicizing backlashes likely to issue, in the case of climate change, in antidemocratically nationalistic and authoritarian responses to the environmental emergency.